Peran Bukti dan Keahlian Dalam Membuktikan Tindak Pidana Yang Berkaitan Dengan Fetishisme Disorder - Evangeline Amanta Chrisya; Firmansyah, Hery (Universitas Ekasakti, 2024)
Fetishism is often hidden and difficult to prove as a criminal offense in Indonesia due to the lack of specific regulations in the Criminal Code. This disorder involves sexual arousal towards non-genital objects and may interfere with social functioning, requiring behavioral therapy. Evidence challenges include difficulty obtaining evidence and social stigma. The solution is clearer laws, specialized law enforcement training, a multi-disciplinary approach, and public education to reduce stigma and increase reporting. The aim of this research is to find out the challenges and solutions in proving criminal acts related to fetishism. The research method used in this article is normative legal research. Normative legal research focuses on the analysis of statutory regulations, legal doctrine, and relevant legal concepts to find solutions to the legal issues raised in this paper. The results of this research are that Fetishistic disorder is a condition where a person has sexual urges towards non-genital objects, which can be a criminal act. In Indonesia, the law does not specifically regulate fetishism, creating a gap in protection for victims. Challenges in evidence include difficulty gathering evidence, social stigma, and lack of understanding. The solution is more comprehensive laws, specialized training for law enforcement, a multi-disciplinary approach, public education, and the use of advanced forensic technology.